1991
DOI: 10.1097/00003446-199110000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Use by Patients Fitted with the lneraid Cochlear Implant

Abstract: A 0 S T R A C TA survey of telephone use by 66 patients fitted with the lneraid cochlear prosthesis revealed that 51% initiate telephone calls (most calls are to family or friends) and that 66% answer the telephone. Of the patients who answer the telephone, 49% indicated that they could identify the gender and/or age of the caller most of the time, 27% could identify a familiar caller most of the time, and 48% indicated that they could understand a conversation most of the time if speaking to a familiar speake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 1 publication
1
10
0
1
Order By: Relevance
“…254 were returned for a response rate of 49%. This response rate is similar to previous studies (Dorman et al, 2001;Cray et al, 2004). Of these 254, 87% of patients were classified as telephone users.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…254 were returned for a response rate of 49%. This response rate is similar to previous studies (Dorman et al, 2001;Cray et al, 2004). Of these 254, 87% of patients were classified as telephone users.…”
Section: Discussionsupporting
confidence: 89%
“…Encouragingly, when phone use in cochlear implant patients is compared to these previous studies, the overall percentage of users has been increasing steady. Dorman et al (2001) reported that 66% used a phone, whereas Cray et al (2004) reported that 70% used the phone. This increasing trend of phone use is encouraging given the positive psychological and sociological benefits it has.…”
Section: Discussionmentioning
confidence: 99%
“…There has been ample demonstration because the early reports of the improvement in threshold and increased closed-set speech discrimination ability (Gantz et al, 1988;Mecklenburg & Brimacombe, 1985). Further, with ongoing refinement in signalprocessing methods (Tyler, 1993;Tyler, Haskell, & Parkinson, 1994), open-set speech recognition (McKay, Vandali, McDermott, & Clark, 1994;Wilson, Lawson, Finley, & Wolford, 1993) and telephone communica-tion (Cohen, Waltzman, & Shapiro, 1989;Dorman, Dove, Parkin, Zacharchuk, & Dankowski, 1991) are becoming more common among implantees.…”
Section: Evolution Of Prosthetic Devicesmentioning
confidence: 99%
“…There are plenty of papers in the scientific literature investigating the ability to perceive telephone speech in CI patients. The first pioneering studies date back to the late 1980s and early 1990s [4]. In these works, mostly based on ad hoc questionnaires, the main problems are first outlined: perception of timbre, making it difficult to differentiate a female voice from a male one; understanding unfamiliar voices, with a greater perceptual difficulty if the communication takes place with a stranger; little/no clues on the discussion topic, whereas its a priori knowledge increases the brain's deductive skill, since the peripheral input signal is poor.…”
Section: Introductionmentioning
confidence: 99%